L’expérience visuelle est-elle une relation ou une représentation ? Le relationnisme et l’intentionnalisme à l’épreuve des sciences cognitives - Jérôme Dokic (Astérion)
The naïve conception of visual experience depicts such experience as a direct, primitive relation between the seeing subject and the object seen. It hinges on an opposition between the visual relation and the mental representation of the object seen in visual imagination or in the vision of images. The aim of this article is to suggest that the naïve opposition between relation and representation is still philosophically and scientifically relevant. Two philosophical theories of perception are presented: Relationalism takes up the spirit of the naïve conception by analysing visual experience as a non-representational relation to the object seen, whereas intentionalism rejects the naïve conception as inadequate and considers visual experience to be representational through and through. After introducing a general notion of representation acceptable to both sides, we examine a body of works from cognitive science that can mediate the debate between relationalism and intentionalism. The main argument propounded is that relationalism is compatible with the scientific data at our disposal on the cognitive processes related to vision. Relationalism has an additional philosophical advantage since it allows us to understand how mental representations, including visual ones, can be based on a more direct cognitive relation – in other words, an intrinsically relational one – to the visible world.